Charge immobilization of the voltage sensor in domain IV is independent of sodium current inactivation - Sheets, Michael F (Blackwell Science Inc, 2005)
Recovery from fast inactivation in voltage-dependent Na(+) channels is associated with a slow component in the time course of gating charge during repolarization (i.e. charge immobilization), which results from the slow movement of the S4 segments in domains III and IV (S4-DIII and S4-DIV). Previous studies have shown that the non-specific removal of fast inactivation by the proteolytic enzyme pronase eliminated charge immobilization, while the specific removal of fast inactivation (by intracellular MTSET modification of a cysteine substituted for the phenylalanine in the IFM motif, ICM(MTSET), in the inactivation particle formed by the linker between domains III and IV) only reduced the amount of charge immobilization by nearly one-half. To investigate the molecular origin of the remaining slow component of charge immobilization we studied the human cardiac Na(+) channel (hH1a) in which the outermost arginine in the S4-DIV, which contributes ∼20% to total gating charge (Q(max)), was mutated to a cysteine (R1C-DIV). Gating charge could be fully restored in R1C-DIV by exposure to extracellular MTSEA, a positively charged methanethiosulphonate reagent. The RIC-DIV mutation was combined with ICM(MTSET) to remove fast inactivation, and the gating currents of R1C-DIV-ICM(MTSET) were recorded before and after modification with MTSEA(o). Prior to MTSEA(o), the time course of the gating charge during repolarization (off-charge) was best described by a single fast time constant. After MTSEA, the off-charge had both fast and slow components, with the slow component accounting for nearly 35% of Q(max). These results demonstrate that the slow movement of the S4-DIV during repolarization is not dependent upon the normal binding of the inactivation particle.